State-dependent action of grayanotoxin I on Na(+) channels in frog ventricular myocytes - Yuki, Tsunetsugu (Blackwell Science Inc, 2001)
1. Distinct properties of grayanotoxin (GTX) among other lipid-soluble toxins were elucidated by quantitative analysis made on the Na(+) channel in frog ventricular myocytes. 2. GTX-modified current (I(GTX)) was induced strictly in proportion to the open probability of Na(+) channels during preconditioning pulses irrespective of its duration, amplitude or partial removal of inactivation by chloramine-T. This confirms that GTX binds to the Na(+) channel exclusively in its open state, while batrachotoxin (BTX) was reported to be capable of modifying slow-inactivated Na(+) channels, and veratridine exhibited voltage-dependent modification. 3. The GTX-modified channel did not show any inactivation property, which is different from reported results with veratridine and BTX. 4. Estimated unbinding rates of GTX were in reverse proportion to the activation curve of GTX-modified Na(+) channels. This was not the previously reported case with veratridine. 5. A model including unbinding kinetics of GTX and slow inactivation of unmodified Na(+) channels in which GTX was permitted to bind only to the open state of Na(+) channels indicated that unbinding reactions of GTX occur only in the closed state.